Development of a fiber Bragg grating interrogation system - Tan, Kian Beng. (2008)
This research looks into the development of a fiber Bragg grating interrogation system in the light of increasing interest in the use of fiber Bragg grating as sensors in various fields such as health monitoring of civil structures. A thorough literature review on the various interrogation techniques is first reported prior to the selection of a suitable interrogation